Effects of anticholinergic challenge on psychopathology and cognition in drug-free patients with schizophrenia and healthy volunteers - Veselinovic, Tanja; Vernaleken, Ingo; Janouschek, Hildegard; Kellermann, Thilo; Paulzen, Michael; Cumming, Paul; Gruender, Gerhard (Psychopharmacology, 2015)
Many aspects of the neurobiology of schizophrenia, especially the physiological basis of the negative symptoms and associated cognitive deficits, remain inadequately understood. Tandon and Greden (1989) postulated a central role of dopaminergic/cholinergic imbalance in schizophrenia.In light of this hypothesis, we elected to investigate the effects of anticholinergic challenge on psychopathology, cognition and attention in 12 unmedicated patients with schizophrenia and 12 healthy controls. The first examination occurred before any pharmacological intervention; the second examination was carried out immediately following an intravenous infusion of 5 mg biperiden, a centrally acting antimuscarinergic agent.The biperiden challenge provoked a considerable increase in PANSS scores in both groups which was significantly more pronounced in patients (repeated measures analysis of variance (ANOVA) (rmANOVA): F(df) = 6.4(1,22); p = 0.019). The increase in the PANSS scores showed a significant negative correlation with age in patients. Biperiden caused considerable cognitive impairments in both groups. A significant group difference (rmANOVA) could be observed for TMT-B (F(df) = 11.29(1,22); p = 0.003).The anticholinergic intervention caused more pronounced psychopathological and cognitive deteriorating effects in patients suffering from schizophrenia than in healthy volunteers. This could be related to the disrupted cholinergic transmission in schizophrenia. Our findings speak on behalf of the need of a more restrictive use of anticholinergics in psychiatric patients. The age-related attenuation of PANSS score increases in patients could be related to the age-dependent changes in dopamine dynamics and also to the age-associated decline of the availability of muscarinic receptors. Our results emphasise the need for further investigation of cholinergic disturbances in schizophrenia.
EVALuna2:13841